Unveiling the Relationship Between ESG Scores and Firm Performance in India: A System GMM Approach - Pruthiranjan Dwibedi; Debasis Pahi; Antarjyami Sahu (Australasian Accounting, Business and Finance Journal, 2024)
This paper investigates the impact of Environmental, Social and Governance (ESG) scores as well as individual pillar scores on the firm performance in the Indian context. Even though a lot of research has been conducted world-wide concerning this issue, a conclusive result has not yet been derived. Being an emerging economy, India is at a nascent stage of research related to ESG issues, and past research indicates a mixed result. In order to avoid the potential endogeneity issue, this paper used a dynamic panel approach of system GMM. This paper considered data from 59 non-financial companies listed under the NSE 500 index. Data was collected from the Thomson Reuters Refinitiv Eikon database over a period of 11, spanning from 2010 to 2021. The finding suggested a significantly negative impact of ESG score on firm performance measured by Tobin's Q and ROA, which indicates a non-linear U-shaped relationship. Net profit margin and closing price are used as alternative, dependent variables to check the robustness of the models and show consistent results. The environmental pillar score and social pillar score showed a negative impact on firm performance, whereas the governance pillar score showed a positive impact on market performance but negatively impacted financial performance. The key takeaway from this paper is that, if firms continue to improve ESG disclosure, it will positively impact firm performance in the future.
Keywords: ESG score; Firm performance; Tobins' Q; ROA; NPM; India; SDG 17.1